1983
DOI: 10.2527/jas1983.5661287x
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Flavors and Performance of Weanling Pigs

Abstract: To characterize the flavor preferences of weanling pigs, a T-maze test was designed and validated. After having sampled feed from one side, containing flavor, and the other side, containing no flavor, pigs were allowed to select feed from either side of the T-maze five times. The frequency of selecting the flavored feed and the percentage of total feed eaten in 20 s/run were used to establish degree of preference for flavors. A total of 129 flavors or flavor combinations was tested in 248 trials, with some fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 1 publication
4
25
0
Order By: Relevance
“…However, an age effect cannot be ruled out since the animals in period II were two weeks older than in period I. It is well known that the susceptibility for flavours declines with age (McLaughlin et al, 1983) which is also seen by Trevisi et al (2007) in the case of thymol. Less frequent feeding behaviour as animals age might also interact with feed preferences.…”
Section: Masking Effect Of Flavours and Camphor To High Thymol Contaimentioning
confidence: 93%
See 1 more Smart Citation
“…However, an age effect cannot be ruled out since the animals in period II were two weeks older than in period I. It is well known that the susceptibility for flavours declines with age (McLaughlin et al, 1983) which is also seen by Trevisi et al (2007) in the case of thymol. Less frequent feeding behaviour as animals age might also interact with feed preferences.…”
Section: Masking Effect Of Flavours and Camphor To High Thymol Contaimentioning
confidence: 93%
“…For example moderate levels of cinnamaldehyde (500 mg/kg), carvacrol (30 mg/kg) and capsicum oleoresin resulted in decreased feed intake post-weaning (Bikker et al, 2003). In general, it has been shown that pigs have prefe-rence for specific flavours, and which, when added to feed, were able to enhance feed intake in the first weak post-weaning (not in the following weeks) (McLaughlin et al, 1983). Hence, the addition of thymol to pig feeds might affect the palatability in one way or the other and have impact on meal initiation and size.…”
mentioning
confidence: 99%
“…In the same study, commercial feed flavors were shown to improve intake of canola meal containing diets by young pigs. Weaned pigs consumed 136 g d -1 of a flavored diet compared with 103 g d -1 of non-flavored diet during week 1 post-weaning, but no differences were noted in subsequent weeks, thus suggesting that the benefit of feed flavors may be limited only to critical periods in the pig's life (McLaughlin et al 1983). Similarly, Campbell (1976 showed increase VFI in piglet during the first week after weaning but not 3 wk after weaning.…”
Section: Ii53 Feed Additivesmentioning
confidence: 99%
“…Swine is one of the most important livestock that provides more than one third of the meat production in the world [3]. Previous research has found that swine favor the bitter taste [4] and therefore, a bitter tasting substance can be used as flavor modifier for addition to swine feed [5].…”
mentioning
confidence: 99%